Nur77 deletion impairs muscle growth during developmental myogenesis and muscle regeneration in mice. - Omar Cortez-Toledo; Caitlin Schnair; Peer Sangngern; Daniel Metzger; Lily C Chao (PLoS ONE, 2017)
Muscle atrophy is a prevalent condition in illness and aging. Identifying novel pathways that control muscle mass may lead to therapeutic advancement. We previously identified Nur77 as a transcriptional regulator of glycolysis in skeletal muscle. More recently, we showed that Nur77 expression also controls myofiber size in mice. It was unknown, however, whether Nur77's regulation of muscle size begins during developmental myogenesis or only in adulthood. To determine the importance of Nur77 throughout muscle growth, we examined myofiber size at E18.5, 3 weeks postnatal age, and in young adult mice. Using the global Nur77-/- mice, we showed that Nur77 deficiency reduced myofiber size as early as E18.5. The reduction in myofiber size became more pronounced by 3 weeks of age. We observed comparable reduction in myofiber size in young myofiber-specific Nur77-knockout mice. These findings suggest that Nur77's effect on muscle growth is intrinsic to its expression in differentiating myofibers, and not dependent on its expression in myogenic stem cells. To determine the importance of Nur77 expression in muscle accretion in mature mice, we generated an inducible-, muscle-specific, Nur77-deficient mouse model. We demonstrated that tamoxifen-induced deletion of Nur77 in 3-month-old mice reduced myofiber size. This change was accompanied by increased activity of Smad2 and FoxO3, two negative regulators of muscle mass. The role of Nur77 in muscle growth was further elaborated in the cardiotoxin-induced muscle regeneration model. Compared to wildtype mice, regenerated myofibers were smaller in Nur77-/- mice. However, when normalized to saline-injected muscle, the recovery of sarcoplasmic area was comparable between Nur77-/- and wildtype mice. These findings suggest that Nur77 deficiency compromises myofiber growth, but not the regenerative capacity of myogenic progenitor cells. Collectively, the findings presented here demonstrate Nur77 as an important regulator of muscle growth both during prenatal and postnatal myogenesis.